Study on the Low Temperature Dielectric Characteristics of Oil Immersed Inverter type Current Transformer - YANG Daiyong; AO Ming; QI Pengshuai; YU Qunying; SUN Yufei (Journal of Harbin University of Science and Technology)
The oilimmersed invertertype current transformer is widely used in power grid because of its advantages. In order to explore the low temperature dielectric properties of the main insulation of the oilimmersed invertertype current transformer, frequency domain dielectric spectroscopy, power frequency loss factor and capacitance of a 35kV oilimmersed invertertype current transformer were tested at low temperature in this paper. The results show that at different temperatures the frequency domain dielectric spectrum of the oilimmersed invertertype current transformer first descends and then rises. When the temperature was below -40℃, the difference of the frequency domain dielectric spectrum of the current transformer is very small and almost coincides at low frequency. The power frequency loss factor of oilimmersed invertertype current transformer increases with the decrease of the test temperature, and the change rate is slow to fast, while the capacitance decreases at a constant speed with the decrease of temperature. According to the results, based on the theory of dielectric physics, the laws of frequency domain dielectric spectroscopy, power frequency loss factor and capacitance at low temperature were analyzed. The test results in this paper have some reference value for the research of low temperature characteristics of oilpaper insulation power equipment.